(untitled) (Research, Society and Development, 2025)
The present research points out the teaching strategies provided in the Specialized Educational Service (SES), which occur within the Multiprofessional Resource Room (MRR) whose purpose is the occurrence of the inclusion of the student with special needs in the regular class. Research objective: To investigate in the literature the challenges of implementing pedagogical strategies for teacher intervention that can be used in SES. Methodology: Narrative Literature Review with a qualitative and descriptive approach. Results: a survey of 20 (twenty) publications was carried out. Discussions: it was found that the specialized educational service is related to the federative policies, bringing the proposal of inclusion of students with special educational needs, emphasizing the National Policy of Special Education in the Perspective of Inclusive Education. The importance of teaching with pedagogical strategies that contributes to the inclusion of the student in the SES is considered, this pedagogical complementation not only occupies an enrollment, but also makes the learning and development of the student effective, through the adaptation of the curriculum, educational pedagogical projects to guarantee the student the monitoring in the regular class, and it is up to them to enjoy the interaction with the other students.